Memoria y soledad: de la Shoá a la violencia colombiana - Canfield, Martha L. (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The essay focuses on a novel by the Colombian writer Azriel Bibliowicz, Migas de pan, published in 2014, that narrates the kidnapping of an elderly Jew who survived the Siberian concentration camps and emigrated in Colombia with his wife, an Auschwitz survivor. Both themes, Holocaust and Colombian Violence, are linked and give rise to a series of reflexions on evil, solidarity, personal memory and its transmission (or post-memory), and the values of words and silence.